FACTORS AFFECTING THE PERCEPTION OF HYGIENE AIMED AT TURKISH HAMAMS AS CULTURAL HERITAGE: ANTALYA - Düriye Bozok; Övgü Açiksözlü; Emin Güleç (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2016)
This study has been carried out in order to identify the factors affecting the perception of hygiene aimed at Turkish Hamams as cultural heritage. With respect to this goal, a survey has been performed by means of a sample method for local and foreign tourists who have used the hamams in the central district of Antalya. In total, 210 people have been reached. The value for Cronbach’s alpha in the survey has been measured as 0.797. In the analysis of research data regarding the statistical method, factor analysis, regression and correlation have been used as analysis methods. As a result of the research done on factors affecting the perception of hygiene aimed at Turkish hamams, the elements such as the sensitivity of hamam personnel on hygiene, the fulfilment in general principles of hamam, and the physical competence of hamam have been identified as the three significant factors by the tourists involved in the survey.